Tradisi Mandi Safar Masyarakat desa Air Hitam Laut Sadu Tanjung Jabung Timur 2003-2023 - Rahmanda Putri, Nopella; Robbi Kurniawanti, Merci; Purnomo, Budi (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
In general, this research aims to describe and find out how the Mandi Safar tradition began in the community of Air Hitam Laut Sadu Village, Tanjung Jabung Timur 2003-2023, the procession of the Mandi Safar tradition of the community of Air Hitam Laut Sadu Village, Tanjung Jabung Timur 2003-2023, and the existence of the Mandi Safar tradition. community of Air Hitam Laut Sadu Village, East Tanjung Jabung 2003-2023. This research uses historical methods consisting of: 1. Heuristics, 2. Source Criticism, 3. Interpretation, and 4. Historiography. The results of the research state that the history of the Safar Bathing tradition began to be carried out by the people of Air Hitam Laut village since 1965, then in 2003 this tradition was officially designated as a regional event by the government. The Safar Bathing process has three essences, first, writing or memorizing seven verses of the Koran starting with the pronunciation of salamun. second, the intention to bathe and third, the bath itself. The existence of the Mandi Safar tradition increases every year and is able to attract thousands of tourists from outside the region and even from outside the province